1998
DOI: 10.1021/ef970113c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Liquefaction of Brown and Subbituminous Coals Using NiMo Sulfide Catalyst Supported on Carbon Nanoparticles

Abstract: Single- and two-stage liquefaction processes of Yallourn (YLC), South Banko (SBC), and Tanitoharum (THC) coals were performed in an autoclave of 50-mL capacity at variable solvent (tetralin)/coal ratios from 0 to 1.5 under the reaction hydrogen pressure of 15 MPa, using NiMo sulfide supported on carbon nanoparticles or commercial NiMo/alumina and synthetic pyrite catalysts. Although the oil yield decreased very much with all the catalysts by reducing the amount of solvent to zero, the NiMo/carbon catalyst gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Interestingly, it was found that the use of a non-donor solvent of anthracene or creosote oils in the presence of Mo catalyst precursors led to a higher liquefaction conversion than that of the donor solvent of tetralin [24]. More interestingly, it was demonstrated by many studies [25][26][27] that water could be an effective co-solvent for coal liquefaction by promoting catalyst dispersion.…”
Section: Solventmentioning
confidence: 99%
“…Interestingly, it was found that the use of a non-donor solvent of anthracene or creosote oils in the presence of Mo catalyst precursors led to a higher liquefaction conversion than that of the donor solvent of tetralin [24]. More interestingly, it was demonstrated by many studies [25][26][27] that water could be an effective co-solvent for coal liquefaction by promoting catalyst dispersion.…”
Section: Solventmentioning
confidence: 99%
“…Fe, Ni, and Mo salts were impregnated onto KB by several impregnating methods using iron(II) fumarate (FeC 4 H 2 O 4 ), Ni(NO 3 ) 2 , or nickel acetate (Ni(OAc) 2 ) and MoO 2 -acetylacetonate (AA) or (NH 4 ) 6 Mo 7 O 24 in methanol or water depending on the solubility of the salts. [9][10][11] The catalysts prepared in the present study are listed Then, the solid in the slurry was recovered by evaporation and dried at 120 °C for 12 h in vacuo. In the case of successive impregnation, nickel was first impregnated followed by iron.…”
Section: Methodsmentioning
confidence: 99%
“…Other combinations of metal precursors, Mo/Ni, Fe/Mo, and Fe/Mo/Ni were also impregnated on KB in the same manner. [7][8][9][10][11][12][13][14][15] The elemental analyses of Indonesian sub-bituminous coals used, namely, Tanito Harum, Adaro, and South Banko coals, are summarized in Table 4. Commercially guaranteed grade tetralin (TL) and 1-methylnaphthalene were used as a liquefaction solvent and a reactant in the hydrogenation, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important direction for improving and enhancing thermoliquefaction of solid organic feedstocks is the use of catalysts that accelerate H 2 formation that, in turn, prevents condensation of the radicals formed during cracking. It was shown that oxides, sulfides, and chlorides of Group VIII, VI, and IV metals are equally as promising as traditional Group VIII metal catalysts [19][20][21][22][23][24][25]. The researchers found that the liquefaction efficiency of brown coal in the presence of molecular H 2 and a catalyst increased in the order Fe < Sn < Zn < Co < Ni.…”
mentioning
confidence: 99%